Paradigma de una nueva era del Turismo y su relación con el ambiente y con las oportunidades de empleo turístico - Meléndez, Anaida (Revista Turismo em Análise, 1996)
This article presents the characteristics of the new tourism paradigm in substitution of the traditional tourism model. It analyze its impact of this in general and individual profesional formation, and presents examples of the new tourism employments. This work brings up the international trend for sustainable development programs and mentions some specific projects, conservation organizations and institutions that offer support for the environment protection.